A Multi-Output Multi-String High-Efficiency WLED Driver Using 40 nm CMOS Technology - Hani H. Ahmad; Fadi R. Shahroury; Ibrahim Abuishmais (Journal of Low Power Electronics and Applications, 2021)
In this work, a multi-independent-output, multi-string, high-efficiency, boost-converter-based white LED (WLED) driver architecture is proposed. It utilizes a single inductor main switch with a common maximum duty cycle controller (MDCC) in the feedback loop. A simple pulse skipping controller (PSC) is utilized in each high-side switch of the multiple independent outputs. Despite the presence of multiple independent outputs, a single over-voltage protection (OVP) circuit is used at the output to protect the circuit from any voltage above 27 V. An open circuit in any of the strings is addressed, in addition to the LED’s short-circuit conditions. Excellent current matching between strings is achieved, despite the low ON-resistance (<semantics>Rdson</semantics>) of transistors used in the 40 nm process. Most circuits are designed in digital CMOS logic to overcome the extreme process variations in the 40 nm node. Compared to a single output parallel strings topology, a <semantics>50%</semantics> improvement in efficiency is achieved relative to extremely unbalanced strings. Three strings are used in this proposal, but more strings can be supported with the same topology. Each string is driven by a 25 mA current sink. An input voltage of 3.2–4.2 V and an output voltage up to 27 V are supported.